Political Ideology and Urban Ideology: the Case of the Modern Movement in Bogota (1930-1950) - Duquino Rojas, Luis Gabriel (Universidad del Rosario, 2016)
This paper aims to build a review to the correspondence between the discourse of political ideology, the discourse of urban ideology and its manifestation in architectural realization. The text generally consists of two main bodies. The first, reviews the process of building the modern movement in architecture and urbanism and then subsequent transit and implementation in Colombia, specifically in Bogotá. It is necessary to note that the political speech to revise is Colombian, although the Modern Movement has a European origin and American developments, the context to review is specifically limited by the interaction of these ideas with the historical-geographical space of Bogotá, embodied in the urban development of the city. Under these rules, the European political considerations are hardly references to contextualize the modern movement itself and its vicissitudes. Also, the definition of the time period of study, which is due to the appearance in the country of the need to consider the problem of urban planning through intellectual exercises grounded in architecture, urbanism and medicine; the latter as a driver of the concepts of modern ideology of healthy living and social hygiene (Ramírez, 2000b)